PEMBERDAYAAN KELOMPOK TANI MELALUI PROGRAM SOSIALISASI PEMANFAATAN SERBUK PENGAWET NABATI DAN KIT UJI TANAH UNTUK MEWUJUDKAN FOOD RESILIENCE - Tanjung, Yulia Windi; Lisa, Oviana; Aminah, Siti; Afrija, Nur; Carlos, Roberto (Jurnal Abdi Insani, 2025)
Food resilience is a shared responsibility between the government and the community to meet the food needs of all Indonesian citizens, particularly from West Aceh. One effort to optimize food resilience is to increase superior natural resources (SDA) such as rice. The use of chemicals to prevent rice weevil pests from attacking rice stores and ineffective fertilization management in rice fields often have negative impacts on both health and the environment. This socialization activity aimed to introduce the use of plant preservative powder as an alternative to controlling rice weevil pests in rice storage and the use of soil test kits to independently measure nutrient conditions in rice fields. This activity was carried out in Peunia Village, Kaway XVI District by involving members of the Ingin Maju Farmers Group as service partners. The results of this empowerment activity showed the importance of understanding the actual condition of the soil through soil analysis using soil test kits, such as pH meters and BWD tools. This knowledge aimed to minimize the possibility of a decline in soil carrying capacity (degradation) which can have an impact on rice production. The production of rice reserves can also be controlled from pest attacks such as rice weevils (Sitophilus oryzae) by using preservative powder made from aromatic leaves. Increasing farmer skills in these two methods were expected to support the realization of food resilience and more sustainable and environmentally friendly agricultural management.